(untitled) (Agroindustria, Sociedad y Ambiente, 2021)
The intentionality of the research is to reveal a vision from the complexity to explain the decision making in community organizations, that is to say, the reality and the construction of knowledge of actions, interactions in constant dialogue, where the opposites are seen as a whole on the premise of creative disorder and linearity for the study of the phenomenal world marked by the hologrammatic character. The empirical scenario is constituted by the El Ujano II Communal Council of Santa Rosa Parish, Iribarren Municipality, and Lara State. As a method Theory Grounded from the perspective proposed by the interpretative construction that proposes the interpretative construction, according to which the original ideas of the Glaser- Strauss proposal and explanations of the feelings of individuals are incorporated to the extent that they experience a phenomenon or process and the beliefs and values of the researcher. The techniques for gathering information come from observation and in-depth interviews. The emerging categories are consensual decision-making, the community leader and competencies for community management. Among the findings, the communal organization stands out as a dynamic and complex system made up of multiple entities and interrelated processes, degrees of uncertainty and multidimensionality of the integrated and adequate human being in the daily construction of consensus for decision-making and community action.